EMPLOYEE ENGAGEMENT DAN MOTIVASI PENGARUHNYA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN WATERBOM BALI - Wayan Arya Paramarta; Ni Luh Suastari (Forum Manajemen STIMI Handayani Denpasar, 2018)
The aims of this study are to analyze the effect of employee engagement and motivation on job satisfaction, to analyze the effect of employee engagement and motivation on employee performance, and to analyze the effect of job satisfaction on employee performance at Waterbom Bali. This study was taken because there are still differences between the research studies with each other. The population in this research is all employees at Waterbom Bali which amounts to 278 people. The sample is determined by proportional area random sampling technique, with 164 respondents. Hypothesis has been observed using Structural Equation Modelling (SEM) with IBM SPSS AMOS 20. The results of this study showed that there was no significant effect between employee engagement on job satisfaction, there is no significant effect between motivation on job satisfaction. There is a significant effect between employee engagement on employee performance. There is a significant effect between the motivation on employee performance. Next, there is no significant effect between job satisfaction on employee performance at Waterbom Bali.